Serum Ferritin in Cirrhosis: The Preliminary Report - Insiripong, Somchai; Wipatagoon, Noppawan; Supattarobol, Tanarat (Maharat Nakhon Ratchasima Hospital Journal, 2024)
Introduction: Primary hemochromatosis is opposed to the hepatitis B virus as the cause of chronic liver diseasesin Thailand. When the cirrhotic patients are shown to have HBsAg, the iron study will be automatically neglected.Patients and Methods: This cross-sectional study was performed to explore the serum ferritin, hepatitis B and Cviruses in the cirrhotic patients who were proved to be free from severe thalassemian or chronic kidney disease.Results: Thirty cirrhotic patients, 15 males, mean age 57.2+9.8 years, were enrolled. The serum ferritin wasfound to range from 15.1 to 9,455, mean 1,685.5+2,335.7 ng/ml, the transferrin saturation ranged from 23.6 to54.8, mean 38.6+8.4% while HBsAg and HCV were found in 6 (20.0%) and 2 patients (6.7%), respectively. Thehyperferritinemia (serum ferritin >1,000 ng/ml) was found in 14 patients (46.7%). Four from 6 patients withHBsAg had the hyperferritinemia but the prevalence was not different from the patients without HBsAg (p=0.272).Conclusion: The hyperferritinemia is found in nearly half cases of cirrhotic patients regardless of hepatitis Bvirus and its prevalence is 2-fold and 7-fold of hepatitis B and C viruses respectively.